Epiphytic lichens and bryophytes of forest ecosystems in Tuscany (Central Italy) (Cryptogamie Mycologie, 1999)
The distribution of epiphytic bryophytes and lichens on three species of trees (Quercus ilex, Quercus cerris and Fagus sylvatica, representing the forest ecosystems of central Italy at low, medium and high elevations, respectively) was examined with respect to host specificity and habitat differences. Although most species were host-specific, the results suggested that habitat characteristics are more important than phorophyte properties in determining the distribution of lichens and bryophytes. Factors affecting the diversity of the epiphytic flora were different for lichens and bryophytes. In the case of lichens, climatic parameters and forest monospecificity were important factors, whereas tree cover (i.e. shade) and to a certain extent the number of available trees seemed more important for bryophytes.

Epiphytic lichens and bryophytes of forest ecosystems in Tuscany (Central Italy) - Loppi, Stefano; Bonini, Ilaria; de Dominicis, Vincenzo (Cryptogamie Mycologie, 1999)
The distribution of epiphytic bryophytes and lichens on three species of trees (Quercus ilex, Quercus cerris and Fagus sylvatica, representing the forest ecosystems of central Italy at low, medium and high elevations, respectively) was examined with respect to host specificity and habitat differences. Although most species were host-specific, the results suggested that habitat characteristics are more important than phorophyte properties in determining the distribution of lichens and bryophytes. Factors affecting the diversity of the epiphytic flora were different for lichens and bryophytes. In the case of lichens, climatic parameters and forest monospecificity were important factors, whereas tree cover (i.e. shade) and to a certain extent the number of available trees seemed more important for bryophytes.
Keywords: distribution (voyant); epiphytic bryophytes; epiphytic lichens; forest ecosystems; Host specificity